Immune Responses Induced by pVAX/TgERK7 against Toxoplasma gondii Infection in BALB/c Mice - Hai-Ting GUO; Zhong-Yuan LI; Jin-Lei WANG; Zhao-Yu GENG; Xing-Quan ZHU (Iranian Journal of Parasitology, 2019)
Background: Toxoplasma gondii can infect all the warm-blooded vertebrates and cause serious toxoplasmosis. Extracellular signal-regulated kinase 7 in T. gondii (TgERK7) mediated the proliferation of this parasite may be a potential vaccine candidate. Thus, immune responses induced by TgERK7 were investigated in this study using a DNA vaccine strategy. Methods: pVAX/TgERK7 plasmid was constructed and used to immunize BALB/c mice for three times with two-week intervals. The challenge and the investigation of humoral and cellular immune responses were performed at two weeks post the last immunization, and the survival times of the infected mice were daily recorded until all of them were dead.